POSTMODERNISME DALAM NOVEL BILANGAN FU KARYA AYU UTAMI - Irma Satriani (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract. Postmodernism in Numbers Novel Fu Works Ayu Utami. Novel Numbers Fu by Ayu Utami theme spiritualism critical form of debate associated with mysticism, superstition, offerings, monotheism, and presenting intertextuality his world through myth Nyi Roro Kidul related to history Babad Tanah Jawi, myths Watugunung, and historical events contradicted by events factual. Utami represent worlds ontological pluralism Zones science fiction, fantastic fiction, and historical realities. This is indicated postmodern fiction novel with ontological issues, so you can find strategies Utami in presenting worlds in it.